A ‘Hero of Old’: Henry Wheeler Robinson, Baptist Old Testament Scholar - Rooke, Deborah W. (Baptist quarterly, 2025)
This article reviews the contribution to the scholarship of Henry Wheeler Robinson, Baptist Old Testament scholar and Principal of Regent's Park College. Robinson's entire academic career was undertaken in the context of denominational ministerial training, and his writings display a strong Christian commitment. At the same time, however, having himself studied during a period of epoch-making developments in biblical studies, Robinson was equally committed to engagement with contemporary scholarship. He insisted that the results of critical scholarship were vital to religion, and indeed, his signature concept of corporate personality in ancient Israel was developed by reading the biblical text in light of contemporary scholarship, to understand the text in terms of its own culture and ideas. Although Old Testament scholarship has moved on and Robinson's specific ideas have been critiqued, his principle of fully embracing critical scholarship as a necessary part of an informed faith nevertheless remains.